Characterization of eDNA from the Clinical Strain Acinetobacter baumannii AIIMS 7 and Its Role in Biofilm Formation - Praveen K. Sahu; Pavithra S. Iyer; Amrita M. Oak; Karishma R. Pardesi; Balu A. Chopade (The Scientific World Journal)
Release of extracellular DNA (eDNA) was observed during in vitro growth of a clinical strain of Acinetobacter baumannii. Membrane vesicles (MV) of varying diameter (20–200 nm) containing DNA were found to be released by transmission electron microscopy (TEM) and atomic force microscopy (AFM). An assessment of the characteristics of the eDNA with respect to size, digestion pattern by DNase I/restriction enzymes, and PCR-sequencing, indicates a high similarity with genomic DNA. Role of eDNA in static biofilm formed on polystyrene surface was evaluated by biofilm augmentation assay using eDNA available in different preparations, for example, whole cell lysate, cell-free supernatant, MV suspension, and purified eDNA. Biofilm augmentation was seen up to 224.64%, whereas biofilm inhibition was 59.41% after DNase I treatment: confirming that eDNA facilitates biofilm formation in A. baumannii. This is the first paper elucidating the characteristics and role of eDNA in A. baumannii biofilm, which may provide new insights into its pathogenesis.